PERAN KEPOLISIAN NEGARA REPUBLIK INDONESIA DALAM MENANGULANGI TERORISME DI DIY (STUDI KASUS TERORISME LAPORAN POLISI NOMOR: LP/A/18/II/2021/SPKT/DENSUS, TANGGAL 14 FEBRUARI 2021) - Panji Bayu Atmaja; Sigit Herman Binaji; Hartanti (Fakultas Hukum Universitas Janabadra, 2024)
The formulation of the problem of this study are: How is the role of the National Police, especially Densus 88 in anticipating terrorism in Yogyakarta? What are the constraints of the National Police, especially Densus 88 in anticipating terrorism in Yogyakarta? This type of research is normative legal research with empirical approach. This study was conducted in the province of Special Region of Yogyakarta, namely in the jurisdiction of the Special Region of Yogyakarta police. The method of data collection in this study is through interviews, literature studies and documentation. The analysis tool used in this study is qualitative data analysis. The results of this study show that the National Police formed an Anti-Terror Task Force called Special Detesamen 88 Anti-terror police (Densus 88/AT), Densus 88/AT also coordinates several institutions, including prisons, DIY police, BNPT, prosecutors and the community, conducting cyber patrols to combat radical understanding on the internet, carrying out repressive actions by arresting perpetrators of acts that meet elements of terrorism. Some of the constraints of the National Police in anticipating acts of terror in Yogyakarta are internal conflicts in the National Police containing the risk of internal conflict, the existence of external obstacles, namely the debate over the duties of the National Police and the TNI, the lack of information from the public related to suspicious people in the surrounding area, not fully standard, both physical and armed resistance and sometimes Densus 88 have to use actions that violate the code of conduct to make arrests due to failed negotiations with terrorists.